The Visual and the Self in Contemporary Poetry - Roberts, Andrew (Romanticism and Victorianism on the Net)

(untitled) (Université de Montréal, 2008)
AbstractThe dominance of the visual is often seen as a new and defining feature of contemporary culture. Yet it is Romantic poetry which most powerfully associates the act of seeing with understanding, self-shaping and the visionary. This article draws on the ideas of the Idealist philosopher J.G. Fichte and the German Romantic writers Novalis and F.W. Schlegel, as well as some of Walter Benjamin’s reading of their work, to explore the ways in which contemporary poetry engages with this Romantic legacy. Making connections with the metaphors of reflection and refraction used by Wordsworth and Coleridge, the article interprets examples of 21st-century post-Romantic text poetry (which revisits Romantic models with an ecological inflection), and digital poetry (which uses technology to reconfigure the relationship between text, self and the visual). More specifically, it proposes a set of relations between visual perception of the natural world, reflective thought and awareness of self in the work of three contemporary poets: Thomas A.Clark (born Greenock, Scotland, 1944), John Burnside (born Dunfermline, Scotland, 1955) and John Cayley (born Ottawa, Canada).